1998
DOI: 10.1080/00405009808658643
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Cellulases to Improve the Sorption Properties of Cellulosic Wound Dressings

Abstract: Staple viscose fibres, of a type commonly used in wound-dressing materials, were treated with a celJuJase complex isolated from Geotricum candidum. Adsorption of cellulase onto the fibre and rates of cellulolytic hydrolysis were measured under the applied-treatment conditions. Changes in fibre properties were measured in terms of their speciHc surface area accessible to N^ and cellulases and in terms of their mean pore radius, moisture regain, degree of swelling, and teasile strength. In particular, it was fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 3 publications
0
11
0
Order By: Relevance
“…However, one study has shown that enzymatic modification of viscose materials can surprisingly increase their ability to absorb bacteria. Tereschenko and Shamolina10 showed that cellulase modification of viscose dramatically increases bacteria sorption of Staphylococcus aureus ( S. Aureus ) from its suspension, from 2 to 90%. Accordingly, they suggested that it may be useful for cleansing infected wounds 10.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, one study has shown that enzymatic modification of viscose materials can surprisingly increase their ability to absorb bacteria. Tereschenko and Shamolina10 showed that cellulase modification of viscose dramatically increases bacteria sorption of Staphylococcus aureus ( S. Aureus ) from its suspension, from 2 to 90%. Accordingly, they suggested that it may be useful for cleansing infected wounds 10.…”
Section: Introductionmentioning
confidence: 99%
“…Tereschenko and Shamolina10 showed that cellulase modification of viscose dramatically increases bacteria sorption of Staphylococcus aureus ( S. Aureus ) from its suspension, from 2 to 90%. Accordingly, they suggested that it may be useful for cleansing infected wounds 10. Infection is one of the most serious complications in wound healing that delays healing progress and makes treatment very difficult.…”
Section: Introductionmentioning
confidence: 99%
“…The major demerit of these dressings is their inability to resist to bacterial infection. Actually, a dressing saturated with wound discharge is a favorable medium for the growth of pathogenic bacteria [6]. This can result in increasing the bioburden of the wound (the levels of bacteria and bacterial products).…”
Section: Chapter 12mentioning
confidence: 99%
“…Since wound dressings are intended for a single external application, the solubility or biodegradability of the polymeric carrier are less important than the function of drug release in an amount sufficient for the desired therapeutic action, which can be achieved by using ionic and labile covalent bonds ruptured in vivo. With respect to the mechanism of action, such polymer-based curative wound dressings are close to transdermal therapeutic systems [11].…”
Section: Wound Dressings Possessing Antimicrobial Propertiesmentioning
confidence: 99%
“…An interesting example is viscose fibers partly hydrolyzed by the enzyme cellulase [11]. The ability of partly hydrolyzed viscose to absorb staphylococci, which is 90% higher as compared to the initial fibers, decreases the degree of wound contamination by these microbes.…”
Section: Wound Dressings Possessing Antimicrobial Propertiesmentioning
confidence: 99%